The correlation between body mass index and the risk of osteoporosis in Acehnese adult females in Zainoel Abidin General Hospital - Nadia Safhira Putri Ananda; Husnah Husnah; Safrizal Rahman (World Nutrition Journal, 2021)
Background: Osteoporosis is a condition in which bone become weak and brittle characterized with lower bone density and quality causing increased risk of fracture. The elderly is the most common group to be affected and female is more prone compared to male. One of modifiable risk factors of osteoporosis is low body mass index or underweight. This study aimed to investigate the correlation between body mass index and the risk of osteoporosis on Acehnese adult females in RSUDZA.Methods: This was an analytic observational-cross sectional study which was completed at the Internal Medicine and Orthopedic Policlinic at Zainoel Abidin General Hospital Banda Aceh from August 27th to September 13th 2019. The sampling method used was nonprobability sampling with accidental sampling technique. The body mass index was obtained by measuring respondents’ height and weight while the risk of osteoporosis was assessed by measuring OSTA Score.Results: Results showed that most of respondents was aged between 40-45 years old (55.4%) and there are 62 respondents (74.7%) with abnormal body mass index consisted of 9 underweight respondents (10.8%), 11 overweight respondents (13.3%), and 42 obese respondents (50.6%). The risk of osteoporosis was dominantly mild (69.9%). There were 7 underweight respondents (77.8) had moderate risk of osteoporosis while 2 underweight respondents had severe risk (22.2%). Meanwhile, 41 obese respondents had mild risk of osteoporosis (97.6%). Correlation test using Spearman showed p value 0.000 (p < 0.05) and rs = -0,731 which means that there is a strong correlation between body mass index and the risk of osteoporosis.Conclusions: Lower body mass index is directly proportional with higher risk of osteoporosis.